Simplified methods for analysis of response to dynamic loading - Hamdan, Fadi; Izzuddin, Bassam A. (Steel Construction Institute, 2002)
'This Technical Note describes the development and verification of a new SDOF model for steel members subject to explosion loading. This document addresses some of the shortcomings of the Biggs method for the response analysis of structures to dynamic loading in general, and to blast loading in particular. A new SDOF model has been developed, which is sophisticated enough to capture the main effects ignored by Biggs, but simple enough for practical application in a design office environment. This Note provides an overview of the problem characteristics as well as the formulation method used in developing the new SDOF method. The details of the new model are then provided, mainly in the form of parametric tables, covering both the bending and catenary states of the elasto-plastic member response."--Knovel.
"This note was compiled by Fadi H. Hamdan. It is based on the work that was carried out by Bassam A. Izzuddin."
Keywords: Blast effect.; Buildings -- Blast effects.; Materials -- Dynamic testing.; elektronické knihy; electronic books